The dynamics of price discovery for cross-listed stocks evidence from US and Chinese markets - Geeta Duppati; Yang Hou; Frank Scrimgeour (Cogent Economics & Finance, 2017)
Purpose: This study examines how, and to what extent the trading of the cross-listed China-backed ADRs on the New York Stock Exchange (NYSE) contributes to the information flow and price discovery for the corresponding cross-listed stocks on the Shanghai Stock exchange (SSE). Design/methodology/approach: The study utilizes the information share, Granger causality test, Vector error correction model, Permanent-Temporary Gonzalo-Granger (PT/GG) method and Bivariate DCC-EGARCH model to examine the price discovery dynamics across the cross-listed stocks. Findings: The Granger causality tests show that there is two-way transmission on feedback between the Chinese and US markets. The effects from NYSE to SSE are larger than the other way round. The Bivariate DCC-EGARCH model test results indicate the volatility spill over from NYSE is larger from the SSE. Practical implications: Results suggest that in contrast to previous studies that showed very little contribution to price discovery by Chinese ADRs on the NYSE, the present study indicates that the contribution to price-discovery of Chinese ADRs on NYSE has increased relative to the past, suggesting the importance of changing time frames and economic situations. Originality/value: The study differentiates between long-term and short-term price discovery effects and finds that home country bias persists in the long term and in the short term the information from the Cross-listed China-backed ADRs on the New York Stock Exchange (NYSE) affects price discovery for SSE stocks.
Keywords: G14; G15; 330; price discovery; cross-listed China-backed ADRs on the New York stock exchange (NYSE); information share; permanent-transitory model; home bias hypothesis and Shanghai stock exchange (SSE)